The Efficacy of the Presentation, Practice, and Production (PPP) Method on the Speaking Skill of the English Learners Community (ELC) Students - Husnaini Husnaini; Amalia Yahya; Nur Inayah Wulandari Putri (Universitas Islam Negeri (UIN) Mataram, 2023)
This research aims to examine the efficacy of the Presentation, Practice and Production (PPP) method in improving the speaking skills of English learners participating in an English club, English Learners Community (ELC) at an Indonesian Junior High School in Palopo, Indonesia. Drawing on a quasi- experimental design involving into two classes; experimental class by using the PPP method and the control class by means of non- PPP method. The data were collected through pre and post of speaking tests and interviews. The statistical evidence showed that the students in the experimental group outperformed their counterparts in the control group, indicating that the PPP method significantly improved the students’ speaking skills which can be seen through independent sample result where the value was 0.000 which lower than 0.05. The interview result also assumed that students felt comfortable and could understand the material well through the application of the PPP method. This research summarized that the use of the PPP method can improve students' speaking skills. This study recommends that future studies can apply the PPP method to improve students' speaking skills in formal or non-formal classes